FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PRILAKU SEKSUAL PRANIKAH PADA REMAJA DI GAMPONG GAJAH KECAMATAN MUTIARA KABUPATEN PIDIE TAHUN 2022 - Salamah; Zaitun; Indah Nazira (Yayasan Nusantara Hasana Berdikari, 2022)
The increase in the number of adolescent sexual behavior is caused by the low knowledge of adolescents about sex and reproductive health where knowledge is one of the components in forming one's attitude. There are several factors that will make teenagers tend to take the wrong attitude. This study aims to determine the relationship between knowledge, lifestyle & family upbringing with premarital sexual behavior in adolescents in Gampong Gajah, Mutiara District, Pidie Regency. The research design was analytic with a cross-sectional approach, the study was conducted in Gampong Gajah, Mutiara District, Pidie Regency in February 2022, the population in the study were all male and female adolescents in Gampong Gajah, aged 16 to 21 years, totaling 58 adolescents. sampling technique using the total population. Data collection was carried out using a questionnaire. Based on the results of the study, it was found that there was a relationship between knowledge and premarital sexual behavior of adolescents with a ρ value of 0.01≤ 0.05, there was a relationship between lifestyle and premarital sexual behavior of adolescents with a value of 0.00, and there was a relationship between parenting and premarital sexual behavior of adolescents with a value of 0.02. ≤ 0.05. It is hoped that the research location can be used as input material in dealing with adolescent premarital sexual behavior problems by increasing knowledge about reproductive health, especially premarital sex.